Autoantigen-specific CD4+ T cells acquire an exhausted phenotype and persist in human antigen-specific autoimmune diseases - Saggau, Carina; Bacher, Petra; Esser, Daniela; Rasa, Mahdi; Meise, Silja; Mohr, Nicola; Kohlstedt, Nora; Hutloff, Andreas; Schacht, Sarah Sophie; Dargvainiene, Justina; Martini, Gabriela Rios; Stürner, Klarissa H.; et al. (Immunity, 2024)
Pro-inflammatory autoantigen-specific CD4+ T helper (auto-Th) cells are central orchestrators of autoimmune diseases (AIDs). We aimed to characterize these cells in human AIDs with defined autoantigens by combining human leukocyte antigen (HLA)-tetramer-based and activation-based multidimensional ex vivo analyses. In aquaporin4-antibody-positive neuromyelitis optica spectrum disorder (AQP4-NMOSD) patients, auto-Th cells expressed CD154, but proliferative capacity and pro-inflammatory cytokines were strongly reduced. Instead, exhaustion-associated co-inhibitory receptors were expressed together with FOXP3, the canonical regulatory T cell (Treg) transcription factor. Auto-Th cells responded in vitro to checkpoint inhibition and provided potent B cell help. Cells with the same exhaustion-like (ThEx) phenotype were identified in soluble liver antigen (SLA)-antibody-autoimmune hepatitis and BP180-antibody-positive bullous pemphigoid, AIDs of the liver and skin, respectively. While originally described in cancer and chronic infection, our data point to T cell exhaustion as a common mechanism of adaptation to chronic (self-)stimulation across AID types and link exhausted CD4+ T cells to humoral autoimmune responses, with implications for therapeutic targeting.
CRIS-Team Scopus Importer:2024-10-18
Keywords: antigen-reactive T cell enrichment; ARTE; autoantigen-specific T cells; autoimmune disease; autoimmune hepatitis; bullous pemphigoid; CD154; CD4 T cell exhaustion; Foxp3; MOGAD; neuromyelitis optica